2020
DOI: 10.1021/acs.inorgchem.0c02954
|View full text |Cite
|
Sign up to set email alerts
|

Dicopper(II) Complexes of p-Cresol-2,6-Bis(dpa) Amide-Tether Ligands: Large Enhancement of Oxidative DNA Cleavage, Cytotoxicity, and Mechanistic Insight by Intracellular Visualization

Abstract: Dicopper complexes of a new p-cresol-2,6-bis(dpa) amide-tether ligand (HL1), [Cu 2 (μ-OH 2 )(μ-1,3-OAc)(L1)](ClO 4 ) 2 (1) and [Cu 2 (μ-1,1-OAc)(μ-1,3-OAc)(L1)]X (X = ClO 4 (2a), OAc (2b)) were synthesized and structurally characterized. 2b rapidly cleaves supercoiled plasmid DNA by activating H 2 O 2 at neutral pH to a linear DNA and shows remarkable cytotoxicity in comparison with related complexes. As 2b is more cytotoxic than HL1, the dicopper core is kept in the cell. A boron dipyrromethene (Bodipy)-modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…In terms of cancercell selectivity, 1 is seven times more selective than a dicopper complex with a p-cresol-amide-tether-dpa ligand. 14 These results indicate that cancer-cell-selectivity depends on the ligand and coordination structure of the dicopper core, and that the toxicity of 1 is enhanced by the DNA-targeting phenanthrene unit independently.…”
Section: Cytotoxicity Of 1 Andmentioning
confidence: 91%
See 2 more Smart Citations
“…In terms of cancercell selectivity, 1 is seven times more selective than a dicopper complex with a p-cresol-amide-tether-dpa ligand. 14 These results indicate that cancer-cell-selectivity depends on the ligand and coordination structure of the dicopper core, and that the toxicity of 1 is enhanced by the DNA-targeting phenanthrene unit independently.…”
Section: Cytotoxicity Of 1 Andmentioning
confidence: 91%
“…N,N′,N″-4,7,10-Tris(tert-butoxycarbonyl)-1,4,7,10-tetraazacyclododecane (5), 4-(N-(8-azido-3,6-dioxaoctyl)carbamoyl)-2-hydroxyisophthalic acid (9), and complex 2 were prepared according to the literature. 13,14,[23][24][25]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these results showed that complexes 1-4 could induce apoptosis in the Bel-7402 cells. 49 Fig. 3 Effects of the cell cycle treated with complex 1.…”
Section: Apoptosis Induced By Complexes 1-4 and The Expression Of The Related Proteinsmentioning
confidence: 99%
“…Of course, the ultimate goal of this diversity lies in the enhancement of the AMSs’ biological activity. Accordingly, these actively ongoing techniques are categorized as follow: i) Preparation of multinuclear complexes wherein the metal cores cooperate to provides an efficient active binding site for biomolecules [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] . ii) Variation of the first coordination sphere towards synthesis of homoleptic and hetroleptic complexes [66] , [67] , [68] , [69] , [70] , [71] .…”
Section: Introductionmentioning
confidence: 99%